Treatment of Guillain-Barre Syndrome: A Review - A. Rajabally, Yusuf (Inflammation & Allergy-Drug Targets (Discontinued), 2012)
Guillain-Barre syndrome is a frequently post-infectious, autoimmune acute inflammatory polyradiculoneuropathy affecting all age groups. It typically results in rapid-onset weakness symmetrically affecting proximal and distal muscles. Cranial muscles are not infrequently affected and respiratory muscle weakness requiring mechanical ventilation occurs in 25% of cases. The incidence is around 1-2 per 100,000/year. Various clinical, electrophysiological and immunological subtypes are described. Plasma exchanges (PE) and intravenous immunoglobulins (IVIg) represent the main treatment options. PE were shown to be effective on rate of recovery in randomized trials. Subsequently further trials have demonstrated the equivalence of IVIg. IVIg are frequently the preferred option for practical reasons. Treatment can result in reversible clinical fluctuations which need to be readily recognized. Although number of PE appears to be optimally of 4, except in mildly affected patients where only 2 may suffice, the dosage of IVIg conventionally administered (2 g/kg) may be sub-optimal in some patients. This may relate to a relationship between IVIg pharmacokinetics and clinical outcome. Studies are under way to evaluate the usefulness of a second IVIg course in severely-affected GBS patients. There is no evidence for use of corticosteroids in GBS. Both IVIg and PE are costly and despite their use and established effectiveness, there is still a need for new treatments to lessen disability. Further research is warranted in optimizing currently available therapies as well as finding others to effectively improve the management of this potentially devastating condition.
Keywords: cerebrospinal fluid